A class of nonlocal impulsive differential equations with conformable fractional derivative - Mohamed Bouaouid; Ahmed Kajouni; Khalid Hilal; Said Melliani (Cubo, 2022)
In this paper, we deal with the Duhamel formula, existence, uniqueness, and stability of mild solutions of a class of nonlocal impulsive differential equations with conformable fractional derivative. The main results are based on the semigroup theory combined with some fixed point theorems. We also give an example to illustrate the applicability of our abstract results.